ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Zulkarnain; Sumaizar; Mukarramah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
The study was conducted to analyze financial distress at 4 Islamic banks listed on the Indonesia Stock Exchange. The four banks became the population and sample in this study, which consisted of PT. Bank Syariah Indonesia Tbk (BRIS), PT. Bank Aladin Syariah Tbk (BANK), PT. Bank BTPN Syariah Tbk (BTPS) and PT. Bank Panin Dubai Syariah Tbk (PNBS). The data used is secondary data from the Financial Services Authority website for 2016-2021. The data analysis technique uses financial distress analysis with the Springate model. The research results obtained that only PT. Bank Syariah Indonesia Tbk (BRIS) for 2016-2021 is in good condition. PT. Bank Aladin Syariah Tbk (BANK) in 2016, 2018 and 2021 with results of S < 0.861 so that it can be declared unhealthy or experiencing financial difficulties. Likewise with PT. Bank BTPN Syariah Tbk (BTPS) also experienced financial difficulties in 2018 and 2018 with an S value <0.862. Then PT. Bank Panin Dubai Syariah Tbk (PNBS) in 2017 and 2021 also obtained an S value <0.862. This is because the Bank obtains a negative profit value or suffers a loss.